ANALISIS PENERAPAN PURCHASING DALAM MENDUKUNG KINERJA OPERASIONAL (STUDI KASUS PT INDO BISMAR ) - Fatimatuzzahro, Silviana; Adiwati, Mei Retno (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
Purchasing strategy plays a crucial role in maintaining the stability of a company's operational performance through effective procurement and supplier relationship management. This study aims to analyze the implementation of purchasing strategy at PT Indo Bismar, with a primary focus on requirements planning, Purchase Order (PO) procedures, internal coordination, and supplier management. This study employed a qualitative descriptive method, where data were obtained through in-depth interviews, participant observation, and documentation studies, then analyzed using a data reduction and presentation model. The results revealed that although the purchasing strategy at PT Indo Bismar has contributed to meeting operational needs, its implementation has not been fully optimized. Key obstacles identified include delays in supplier deliveries, discrepancies in inventory data between physical warehouse and administrative records, and a lack of systematic integration in inter-divisional coordination. These findings confirm that the effectiveness of the current strategy is still limited by weaknesses in information management and performance evaluation. It is concluded that improving information system integration and strengthening cross-functional coordination are essential to ensure data accuracy and timely procurement to support the company's sustainable operational performance. ABSTRAK Strategi purchasing memegang peranan krusial dalam menjaga stabilitas kinerja operasional perusahaan melalui pengelolaan pengadaan dan hubungan pemasok yang efektif. Penelitian ini bertujuan untuk menganalisis penerapan strategi purchasing pada PT Indo Bismar, dengan fokus utama pada perencanaan kebutuhan, prosedur Purchase Order (PO), koordinasi internal, serta manajemen pemasok. Penelitian ini menerapkan metode deskriptif kualitatif, di mana data diperoleh melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi, kemudian dianalisis menggunakan model reduksi dan penyajian data. Hasil penelitian mengungkapkan bahwa meskipun strategi purchasing di PT Indo Bismar telah berkontribusi pada pemenuhan kebutuhan operasional, implementasinya belum sepenuhnya optimal. Kendala utama yang teridentifikasi meliputi keterlambatan pengiriman pemasok, ketidaksesuaian data stok antara fisik gudang dan catatan administrasi, serta kurangnya integrasi sistematis dalam koordinasi antar divisi. Temuan ini menegaskan bahwa efektivitas strategi saat ini masih dibatasi oleh kelemahan dalam pengelolaan informasi dan evaluasi kinerja. Disimpulkan bahwa peningkatan integrasi sistem informasi dan penguatan koordinasi lintas fungsi sangat diperlukan guna menjamin akurasi data dan ketepatan waktu pengadaan demi mendukung kinerja operasional perusahaan secara berkelanjutan.